CD4 T Follicular Helper Cells Prevent Depletion of Follicular B Cells in Response to Cecal Ligation and Puncture - Taylor, Matthew D.; Brewer, Mariana R.; Nedeljkovic-Kurepa, Ana; Yang, Yihe; Reddy, Kalpana S.; Abraham, Mabel N.; Barnes, Betsy J.; Deutschman, Clifford S. (Frontiers in Immunology, 2020)
Recent studies have demonstrated that induction of a diverse repertoire of memory T cells (“immune education”) affects responses to murine cecal ligation and puncture (CLP), the most widely – used animal model of sepsis. Among the documented effects of immune education on CLP are changes in T cell, macrophage and neutrophil activity, more pronounced organ dysfunction and reduced survival. Little is known, however, about the effects of CLP on B cell responses, and how these responses might be altered by immune education. Importantly, effective B cell responses are modulated by IL21 produced by CD4+/CXCR5+/PD1+ T follicular helper (Tfh) cells. We examined the B cell population in control and immune educated mice 24 hrs. and 60 days after CLP. Education alone increased Tfh cells. Twenty-four hours after CLP, Tfh cells were depleted. However, this reduction was less pronounced in immune educated mice than in controls and the percentage of CD4 T cells expressing a Tfh phenotype increased in the animals. CLP did not alter splenic architecture and decreased numbers of follicular, marginal and germinal center B cells. CLP induced changes were not, however, noted following CLP in immune educated mice. At 60 days post – CLP, numbers of follicular, germinal center and marginal zone B cells were increased; this increase was more pronounced in immune educated mice. Finally, while CLP reduced the induction of antigen specific B cells in controls, this response was maintained following CLP in immune educated mice. Our data suggest that preexisting Tfh assists in rescuing the B cell response to CLP.